[Letters and Memos regarding CTJ and excise taxes] - FRED PANZER (Tufts Archival Research Center, 2007)
Memo from Fred Panzer to Robert Lewis regarding letter to Rep. John Duncan from Citizens for Tax Justice (CTJ) and Duncan's response. Accuses cigarette tax of being unfair, especially to low income communities. Demonstrates Duncan's support of CTJ's position. Expresses content with CTJ's support in the Tobacco Institute's fight against cigarette tax increases.